2020
DOI: 10.1007/s13178-020-00483-5
|View full text |Cite
|
Sign up to set email alerts
|

Child Development in Same-Sex Families: Beliefs of Chinese Lesbians, Gays, and Heterosexuals

Abstract: Introduction Same-sex parenting remains controversial, with many arguing that it negatively impacts children's psychological and social development. This study investigated the influences of beliefs about the etiology of homosexuality (as either learned or genetic) and ambivalent sexism (benevolent and hostile) on beliefs about children's development in same-sex families. Methods A Chinese sample of 1400 respondents completed an online questionnaire in March-July 2019 and February 2020. The respondents self-id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Hostile sexism is also associated with negative attitudes towards non-traditional family planning, such as surrogacy 162 . However, there is little research on how ambivalent sexism influences minority sexual relationships 163 , 164 . Furthermore, the Ambivalent Sexism Inventory produces different means and item loadings across heterosexual individuals and sexual-minority individuals 46 .…”
Section: Effects On Heterosexual Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hostile sexism is also associated with negative attitudes towards non-traditional family planning, such as surrogacy 162 . However, there is little research on how ambivalent sexism influences minority sexual relationships 163 , 164 . Furthermore, the Ambivalent Sexism Inventory produces different means and item loadings across heterosexual individuals and sexual-minority individuals 46 .…”
Section: Effects On Heterosexual Relationshipsmentioning
confidence: 99%
“…For example, little is known about how ambivalent sexism influences wellbeing and relationship functioning in same-sex couples. There is evidence that sexism contributes to intimate partner violence 163 , attitudes towards same-sex parenting 164 and objectification 170 by sexual-minority individuals and within minority sexual relationships. However, these studies used a measure that is now known not to adequately capture sexism in these populations 46 .…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…E. Whitley, 2001) or HS (Uluboy & Husnu, 2020), and some pointed to differences in these associations depending on the participants’ gender (J. L. Nagoshi et al, 2008; Rye et al, 2019) or sexual orientation (López-Sáez et al, 2020a; Warriner et al, 2013; Zhao & Zheng, 2021), targets’ gender (C. T. Nagoshi et al, 2019), and social context (Buck & Obzud, 2018; Gulevich et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Some of these articles examined prejudiced views of sexual and gender minorities and showed that ambivalent sexism is positively associated with negative attitudes (e.g., Pistella et al, 2018), stereotypes (e.g., Morrison & Bearden, 2007), or affect (e.g., Davies, 2004) toward gay, lesbian, and transgender people, as well as lower support for the rights of these groups (e.g., Masser & Abrams, 1999). Although some of these articles indicated these associations for both HS and BS (e.g., Masser & Abrams, 1999;Pistella et al, 2018), some obtained specific associations with either BS (B. E. Whitley, 2001) or HS (Uluboy & Husnu, 2020), and some pointed to differences in these associations depending on the participants' gender (J. L. Nagoshi et al, 2008;Rye et al, 2019) or sexual orientation (Lo ´pez- Sáez et al, 2020a;Warriner et al, 2013;Zhao & Zheng, 2021), targets' gender (C. T. Nagoshi et al, 2019), and social context (Buck & Obzud, 2018;Gulevich et al, 2021). Yet, slightly more evidence indicates that BS is a better predictor of sexual and gender minority prejudice than HS (e.g., Gulevich et al, 2021;B.…”
Section: Notementioning
confidence: 99%